Optimization and characterization of glycolysis of waste polyethylene terephthalate (PET) with polyethylene glycol (PEG) - Raman, Dinesh Kumar (2013)
Chemical recycling of poly(ethylene)terephthalate(PET)has been the subject of increased interest as a valuable feedstock for different chemical processes.In this research, the glycolysis of PET will be studied using excess Polyethylene Glycol(PEG)as depolymerization agent assisted by magnesium acetate as catalyst.The influence of several operating conditions covering temperature(165–215 ◦C), reaction time(0–4 h),and catalyst concentration and PEG to PET weight ratio was analyzed.The purified monomer was characterized by Differential Scanning CalorimetryDSC), Thermogravimetric Analysis TGA),and Fourier Transform Infrared Spectroscopy(FTIR).Response surface methodology (RSM)software was used to predict the optimal condition of glycolysis process.The optimal condition of glycolysis time, temperature,amount of catalyst and amount of PEG were 205◦C, 2.49hr, 0.12g(2.4wt% of PET used)and 36.87g of PEG respectively.Where using this optimized condition the yield of the process can be reached up to 96.3%.